Efeitos das surpresas de lucros no uso de informações non-GAAPS como estratégia para o gerenciamento de impressões - Nascimento Neto, Antonio Martins do (2023)
The present research aimed to observe the level of usage of non-GAAP indicators as an impression management strategy in the face of earnings surprises. Based on disclosure and signaling theories, the study utilized a sample of 157 Brazilian publicly traded companies listed on the B3 - Bolsa, Brasil e Balcão, which reported non-GAAP indicators in their press releases between the years 2011 and 2022. Information regarding non-GAAP indicators was collected from the corporate press releases' homepages, while other variables were obtained from the Refinitiv Eikon secondary database. Impression management measurement was carried out using the model developed by Brennan, Guillamon-Saorin, and Pierce (2009), examining how non- GAAP indicators were presented in their respective communications. The Earnings Surprise variable was estimated based on the relationship between forecasted earnings per share and earnings per share actually earned by companies. Earnings surprise was classified as positive when entity results exceeded market analysts' predictions and negative when they fell below forecasts. Additionally, the study observed the influence of accruals-based earnings management and real operational activities on estimating earnings surprises and how non-GAAP information was reported. The study's results demonstrated that companies with positive earnings surprises under a low level of earnings management are more likely to disclose non-GAAP information under impression management strategies. Meanwhile, companies that did not meet analyst projections or engaged in high levels of earnings management tended to report indicators discreetly or implicitly. Thus, the study suggests that non-GAAP information represents an organizational strategy to signal positive performance to the market with low indications of opportunistic manipulation. Furthermore, the study finds that impression management practices serve as a substitute tactic for earnings management, as entities that managed their earnings aggressively are less inclined to emphasize non- GAAP indicators, avoiding certain disclosure costs, such as the reduction of the company's market value.